Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Operasional Lembaga Perkreditan Desa di Kecamatan Kediri Kabupaten Tabanan - Rastana, I Dewa Gede; Guna, I Nyoman Ariana; Sarjana, I Wayan Mula (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2023)
The Village Credit Institution (LPD) has a major role in managing village finances. So this institution must continue to be developed. There are many factors that affect the income of Village Credit Institutions in Kediri District, including the amount of credit, the amount of capital and the number of credit customers. The purpose of this study was to determine the effect of the amount of credit, the amount of capital and the number of credit customers on the operational income of the Village Credit Institution in Kediri District, either partially or simultaneously. This study uses three independent variables, namely the amount of credit (X1), the amount of capital (X2), and the number of credit customers (X3) and the dependent variable is operating income (Y) using quantitative analysis methods using linear regression analysis techniques. multiple. The results of this study are (1) the amount of credit has a real and partial significant effect on operational income at the Village Credit Institution (LPD) in Kediri District because t count is greater than t table or 3.643 > 1.739 and the significance is smaller than 0.05, namely 0.002 < 0.05. (2) The amount of capital has a significant and significant effect partially on operating income at the Village Credit Institution (LPD) in Kediri District because t count is greater than t table or 6.615 > 1.739 and the significance is smaller than 0.05, i.e. 0.000 < 0.05 . (3) The number of credit customers has a significant and significant effect partially on the operational income of the Village Credit Institution (LPD) in Kediri District because t count is greater than t table or 4.449 > 1.739 and the significance is smaller than 0.05 or 0.000 < 0.05 . (4) The amount of credit, the amount of capital and the number of credit customers simultaneously have a real and significant effect on the operational income of the Village Credit Institution in Kediri District because the F ratio is greater than F table or 355,046 > 3.20 and the significance is less than 0.05 ie 0.000 < 0.05. Based on the conclusions from the results of the study, it can be recommended to increase the amount of credit, the amount of capital, and the number of credit customers so that it continues to be increased while still paying attention and considering the principle of prudence, especially in providing loans and looking at the business processes of borrowing customers, so that non-performing loans can be minimized as much as possible. traffic jams), as well as more appropriate policies from the government to provide a more conducive climate for the development of Village Credit Institutions (LPD) in the future.